2017
DOI: 10.15389/agrobiology.2017.4.658eng
|View full text |Cite
|
Sign up to set email alerts
|

Domain Distribution of Mobile Genetic Elements in the Bovine Genome

Abstract: Genetic landscape of bovine genome attracts a lot of attention in recent years. This is due to the complexity of genomic selection task solution, i.e. the use of multilocus genotypes in order to simplify and hasten breeding. Accumulated data show that there is high evolutionary speed of different genetic elements and also they have structure functional polymorphism intensity (L. Chen et al., 2017). It was shown that interspersed repeats account for about 50 % of nucleotide sequence of the bovine genome (R.L. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
22

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 21 publications
0
3
0
22
Order By: Relevance
“…It is well known that approximately 50% of nucleotide sequences of cattle genomes are represented by dispersed repeats, mostly retrotransposons (Elsik et al, 2009). Using Repeat Masker database of mobile genetic elements and Integrated Genome Browser software, we analyzed the organization of mobile genetic elements and their recombination products in the first chromosome of cattle nucleotide sequences (13,436,028 bp) (Glazko et al, 2017) Using Integrated Genome Browser software, the co-localization of three-member products of recombination between LINE and LTR ERV and structural genes was studied. It appeared that 34 of these products were located inside 12 genes (and the rest in intergenic regions), while 10 and 12 copies of them were located in two genes -grik1 and арр, functioning in central nervous system pathways in mammals.…”
Section: Role Of Mobile Elements In Domesticationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that approximately 50% of nucleotide sequences of cattle genomes are represented by dispersed repeats, mostly retrotransposons (Elsik et al, 2009). Using Repeat Masker database of mobile genetic elements and Integrated Genome Browser software, we analyzed the organization of mobile genetic elements and their recombination products in the first chromosome of cattle nucleotide sequences (13,436,028 bp) (Glazko et al, 2017) Using Integrated Genome Browser software, the co-localization of three-member products of recombination between LINE and LTR ERV and structural genes was studied. It appeared that 34 of these products were located inside 12 genes (and the rest in intergenic regions), while 10 and 12 copies of them were located in two genes -grik1 and арр, functioning in central nervous system pathways in mammals.…”
Section: Role Of Mobile Elements In Domesticationmentioning
confidence: 99%
“…It is well known that approximately 50% of nucleotide sequences of cattle genomes are represented by dispersed repeats, mostly retrotransposons (Elsik et al, 2009). Using Repeat Masker database of mobile genetic elements and Integrated Genome Browser software, we analyzed the organization of mobile genetic elements and their recombination products in the first chromosome of cattle nucleotide sequences (13,436,028 bp) (Glazko et al, 2017). In this region, SINE/tRNA-Core-RTE, LINE/RTE-BovB, LINE/L1, and LTR/ERV were the most frequent elements.…”
Section: Role Of Mobile Elements In Domesticationmentioning
confidence: 99%
“…Difficulties in the description of multicellular organism regulatory networks are based on the high frequency of recombination of retrotransposons that make up a significant part of the eukaryotic genome [4]. Earlier we identified recombination products between the long interspersed nuclear element (LINE) and endogenous retrovirus (ERV) in the bovine chromosome 1 nucleotide sequence region of 13436028 in length [5]. It was found that 30 RTE-BovB/BTLTR1/RTE-BovB constructions are localized in the intronic regions of 12 structural genes and have a high percent identity (not lower than 78,32%).…”
Section: Introductionmentioning
confidence: 99%
“…Отечественными учеными доказана эффективность применения в животноводстве кормовых добавок на основе макро-и микроэлементов, которые положительно влияют на физиологический статус животных и на продуктивность [1][2][3][4][5][6]. На данный момент предпочтение отдается комплексным препаратам в связи с тем, что данные препараты обладают большей биологической доступностью, что, в свою очередь, позволяет снизить уровень дачи препарата, получая при этом должный результат.…”
Section: Introductionunclassified
“…Помимо этого они оказывают многостороннее и существенное воздействие на многие свойства черноземов, улучшая показатели структурного состояния, плотности сложения и гумусового состояния почв. [1][2][3][4]. В условиях резко континентального засушливого климата в зоне сухой степи на черноземах южных Северного Казахстана первостепенными задачами остаются накопление и сохранение почвенной влаги, предотвращение процессов деградации почв, что возможно лишь при рациональном землепользовании, в том числе за счет создания полезащитных лесных полос.…”
Section: Introductionunclassified